Improvement of Bacillus clausii cell HH1 density via culture medium optimization and pH-stat fed batch fermentation - Pham, Tuan Anh; Nguyen, Thi Phuong; To, Kim Anh (Vietnam Journal of Science and Technology, 2023)
In this study, the culture medium and fermentation modes were studied aiming to improve the cell density of Bacillus clausii. Firstly, the factorial design method using Minimum Run Resolution IV design was used to evaluate the relative importance of culture medium components to the growth of Bacillus clausii. The results showed that three components peptone, yeast extract and malt extract were the components significantly affecting the bacterial biomass. Then, the optimization of these three ingredient concentrations using a response surface methodology with the Box-Behnken design resulted that the maximal biomass had been achieved using the medium containing 7.64 g/L peptone, 10 g/L yeast extract and 6.36 g/L malt extract. Finally, the pH-stat fed batch fermentation was conducted in a 2-liter bioreactor where the 9X concentrated optimal culture medium was feed into the bioreactor based on the pH signal. As a result, the microbial cell density increased by 2.9-fold compared to that achieved through batch fermentation.